A CROSS-SECTIONAL STUDY ON LONG-TERM EFFECTS OF LIGATION OF INTER-SPHINCTERIC FISTULA TRACT (LIFT) FOR TREATING TRANS-SPHINCTERIC ANAL FISTULA. - Jai Prakash Sinha; Kunal (Student's Journal of Health Research Africa, 2024)
Background The Ligation of Inter-Sphincteric Fistula Tract (LIFT) procedure represents a significant advancement in the treatment of trans-sphincteric anal fistulas (TSAF), balancing effective treatment with the preservation of sphincter integrity. The technique primarily aims to maintain continence while achieving a high rate of healing by identifying and ligating the fistula tract within the intersphincteric space, thereby minimizing damage to the sphincter muscles. The study seeks to estimate the long-term efficacy and outcomes of the LIFT procedure as a management strategy for TSAF. Methods A cross-sectional study was carried out and involved sixty participants with trans-sphincteric peri-anal fistulas of cryptoglandular origin confirmed by MRI fistulogram were included. The surgical procedure involved identifying, ligating, transecting, and excising the fistula tract within the inter-sphincteric space. Data on peri-operative infection rates, healing time, discomfort levels, fecal continence, and recurrence rates were collected and analyzed using SPSS software version 22. Results The study included 60 participants (40 males, 20 females) with an average age of 42.5 years. The average healing time post-surgery was 32.4 days. The peri-operative infection rate was 8.3%, and the recurrence rate was 5%. No significant changes were noted in fecal continence post-surgery (p=0.43). The degree of discomfort and recovery time had a strong positive link, according to Pearson's correlation test. Conclusion The LIFT procedure is an effective and safe treatment option for TSAF, demonstrating high healing rates, low recurrence, and preservation of continence. Recommendations Future research should explore modifications of the LIFT technique to further reduce discomfort and improve healing times. Long-term follow-up studies are recommended to assess the durability of surgical outcomes.